Pengaruh Kepemilikan Institusional, Struktur Aktiva dan Profitabilitas Terhadap Struktur Modal - Wardani, Andini Sukma; Minanari, Minanari (Baca Dulu Publisher, 2024)
This research principle aims to examine the influence of institutional ownership, asset structure and profitability on the capital structure of health sector companies listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. This research was conducted with a sample size of 20 companies. Furthermore, testing in this research use multiple regression analysis with a probability sampling method with using IBM SPSS 26. The results of this research explain that institutional ownership and asset structure have no effect on capital structure, and profitability has a negative effect on capital structure.